Construct Validity of the Psychosis Screening Questionnaire in Ugandan Adults - Kwagala, Claire; Kyebuzibwa, Joseph; Okura, Rogers; Akena, Dickens (Research Square, 2023)
Psychotic disorders are common and contribute significantly to morbidity and mortality of people with psychiatric diseases. Therefore, early screening and detection may facilitate early intervention and reduce adverse outcomes. Screening tools that lay persons can administer are particularly beneficial in low resource settings. However, there is limited research evaluating the validity of psychosis screening instruments in Uganda. We aimed to assess the construct validity and psychometric properties of the Psychosis Screening Questionnaire (PSQ) in Uganda in a population with no history of a psychotic disorder.